Targeted therapies in liver fibrosis: combining the best parts of platelet derived growth factor BB and interferon gamma - Dijk, Fransien v.; Olinga, Peter; Poelstra, Klaas; Beljaars, Leonie (Frontiers in Medicine, 2015)
Cytokines, growth factors and other locally produced mediators play key roles in the regulation of disease progression. During liver fibrosis, these mediators orchestrate the balance between pro- and antifibrotic activities as exerted by the hepatic cells. Two important players in this respect are the profibrotic mediator platelet derived growth factor BB (PDGF-BB) and the antifibrotic cytokine interferon gamma (IFNγ). PDGF-BB, produced by many resident and infiltrating cells, causes extensive proliferation, migration and contraction of hepatic stellate cells (HSCs) and myofibroblasts. These cells are the extracellular matrix producing hepatic cells and they highly express the PDGFβ-receptor. On the other hand, IFNγ is produced by natural killer cells in fibrotic livers and is endowed with pro-inflammatory, antiviral and antifibrotic activities. This cytokine attracted much attention as a possible therapeutic compound in fibrosis. However, clinical trials yielded disappointing results because of low efficacy and adverse effects, most likely related to the dual role of IFNγ in fibrosis. In our studies, we targeted the antifibrotic IFNγ to the liver myofibroblasts. For that, we altered the cell binding properties of IFNγ, by delivery of the IFNγ-nuclear localization sequence to the highly expressed PDGFβ-receptor using a PDGFβ-receptor recognizing peptide, thereby creating a construct referred to as “Fibroferon” (i.e. fibroblast-targeted interferon γ). In recent years, we demonstrated that HSC-specific delivery of IFNγ increased its antifibrotic potency and improved its general safety profile in vivo, making Fibroferon highly suitable for the treatment of (fibrotic) diseases associated with elevated PDGFβ-receptor expression. The present review summarizes the knowledge on these two key mediators, PDGF-BB and IFNγ, and outlines how we used this knowledge to create the cell-specific antifibrotic compound Fibroferon containing parts of both of these mediators.